Mono- and tetra-nuclear copper complexes bearing bis(imino)phenoxide derived ligands: catalytic evaluation for benzene oxidation and ROP of ε-caprolactone - Wang, Xue; Zhao, Ke-Qing; Elsegood, Mark R. J.; Prior, Timothy J.; Liu, Xiaoming; Wu, Li; Sanz, Sergio; Brechin, Euan K.; Redshaw, Carl (RSC advances, 2015)
Complexes of the type [Cu(L)₂] (1) and [Cu₄L₂(μ₄-O)(OAc)₄] (2) have been obtained from the reaction of the phenoxydiimine 1,3-(2,6-R²₂C₆H₃N=CH)₂-5-R¹ C₆H₂OH-2 (LH) (where R¹ = Me, tBu, Cl; R² = Me, iPr) with copper(II) acetate [Cu(OAc)₂]; changing the molar ratio of the reactants affords differing amounts of 1 or 2. Reaction of the parent dialdehyde [1,3-(CHO)₂-5-MeC₆H₂OH-2] with [Cu(OAc)₂] in the presence of Et₃N afforded, following work-up, a polymeric chain (3) comprising {[Cu₂(OAc)₄]OAc}n, HNEt₃ and MeCN. The crystal structures of 1 (R¹ = Me, R² = iPr 1a; R¹ = Cl, R² = iPr 1b), 2 (R¹ = Me, R² = Me 2a; R¹ = Me, R² = iPr 2b; R¹ = tBu, R² = Me 2c; R¹ = Cl, R² = Me 2d; R¹ = Cl, R² = iPr 2e; R¹ = tBu, R² = iPr 2f) and 3 are reported (synchrotron radiation was necessary for 3). The magnetic properties of the cluster 2b are presented. Complexes of type 2 and 3 were screened for the ring opening polymerization (ROP) of ε-caprolactone, with or without benzyl alcohol present, under a variety of conditions, however only trace polymer was isolated. The electrochemistry of all complexes was also investigated, together with their ability to catalyze benzene oxidation (using hydrogen peroxide); although low conversions were observed, the tetra-nuclear complexes exhibited excellent selectivity.
Keywords: Ring opening polymerization; Bis(imino)phenoxide derived ligands; ε-caprolactone; Benzene oxidation